Huang Hsiao, Katharine H.Y., Money and Banking in the Chinese Mainland, Taipei, Chung-Hua Institution for Economic Research, 1984, VIII + 98 pp. (Mainland China Economic Series núm. 1). - Cornejo Bustamante, Romer (Estudios de Asia y África, 1986)
-